Modeling of The Effect of Grain Size and La2O3 Doping on Sintering Î± â€“ Cristobilite - Shehab, Alia A.; Farid, Saad B.; Hassun, Hanan K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research the effect of grain size and effect of La2O3 doping on densification  rate for the  initial and intermediate  stages of sintering were studied .The experimental results for Î± â€“ cristobilite powder are modeled using ( L2-Regression ) technique in studying  the effect of grain size and La2O3 doping using  three particles size (6.12, 8.92, 13.6 ) Âµm, with undoped  initial powder and with La2O3 doping . The mathematical simulation showes that the densification rates increase as the initial particles sizes decrease and vice versa. This shows that the densification depends directly on the initial compact density which reflects the contacts area between the particles . However the densification rates in the intermediate stages were enhanced compared with that of the initial stage .This is due to completion of neck growth that facilitates  the mass transport between the grains ,and also, the presence of the massive grains due to the grain growth .                                                                                     Al so it is show that the doping enhances the densification rates in the intermediate stage due to that , the dopants act  against the grain boundaries movement causing discourage closing of porosity and encourage escaping of voids enhances the densification rates .